Structure solution with ARCIMBOLDO using fragments derived from distant homology models. (6th September 2014) - Sammito, Massimo; Meindl, Kathrin; de Ilarduya, Iñaki M.; Millán, Claudia; Artola‐Recolons, Cecilia; Hermoso, Juan A.; Usón, Isabel
<x xml:space="preserve">Abstract</x> Molecular replacement, one of the general methods used to solve the crystallographic phase problem, relies on the availability of suitable models for placement in the unit cell of the unknown structure in order to provide initial phases. ARCIMBOLDO, originally conceived for ab initio phasing, operates at the limit of this approach, using small, very accurate fragments such as polyalanine α‐helices. A distant homolog may contain accurate building blocks, but it may not be evident which sub‐structure is the most suitable purely from the degree of conservation. Trying out all alternative possibilities in a systematic way is computationally expensive, even if effective. In the present study, the solution of the previously unknown structure of MltE, an outer membrane‐anchored endolytic peptidoglycan lytic transglycosylase from Escherichia coli, is described. The asymmetric unit contains a dimer of this 194 amino acid protein. The closest available homolog was the catalytic domain of Slt70 (PDB code 1QTE). Originally, this template was used omitting contiguous spans of aminoacids and setting as many ARCIMBOLDO runs as models, each aiming to locate two copies sequentially with PHASER. Fragment trimming against the correlation coefficient prior to expansion through density modification and autotracing in SHELXE was essential. Analysis of the figures of merit led to the strategy to optimize the search model against the experimental data now implemented within ARCIMBOLDO‐SHREDDER (http://chango.ibmb.csic.es/SHREDDER). In this strategy, the initial template is systematically shredded, and fragments are scored against each unique solution of the rotation function. Results are combined into a score per residue and the template is trimmed accordingly.